KEPASTIAN HUKUM BAGI PARA PIHAK YANG TIDAK DAPAT MENANDATANGANI AKTA NOTARIS SEBAGAI DASAR PENYELESAIAN SENGKETA MELALUI ARBITRASE - Dharma Saputra, Komang Edy; Dyanthi, Luh Merry; Suandika, I Nyoman (Universitas Mahendradatta, 2025)
To determine legal certainty in an agreement, it can be analyzed through the greatest potential cause of disputes in the agreement, namely default. Default is the greatest potential for a problem or dispute in an agreement. Default is the implementation of obligations that are not fulfilled or broken promises or negligence carried out by the debtor either because they do not carry out what has been promised or even do something that according to the agreement should not be done. The term default comes from Dutch, namely